Comparative evaluation of ion release in bonded and nonbonded stainless steel brackets with use of different mouthwashes: An In vitro study - D P Shruthi; G S Patil; D R Prithviraj (Wolters Kluwer Medknow Publications, 2020)
Background: Orthodontic treatment is a long-term procedure that involves the usage of brackets and archwires which are mainly metallic in nature. This study evaluated the levels of metal ions release from bonded and nonbonded orthodontic brackets after immersion in distilled deionized water and three different types of mouthwash. Materials and Methods: Eighty premolar stainless steel brackets (3M, Unitek) were divided into Group A (bonded brackets) and Group B (nonbonded brackets). Each group was further subdivided into four subgroups to analyze the release of ions from three different types of mouthwash along with the control group. All the samples were incubated at 37°C for 45 days, and immersion solutions were tested in inductively coupled plasma-optical emission spectrometer for the release of free metal ions. Results: Mean ion release in the bonded bracket group was less than that of nonbonded bracket group. Ion release in control subgroup of both groups was 0.18 ± 0.08 μg/dl (A1) and 0.17 ± 0.06 μg/dl (B1); in Phos-Flur mouthwash subgroup was 0.12 ± 0.06 μg/dl (A2) and 0.13 ± 0.05 μg/dl (B2); in chlohex mouthwash subgroup was 0.13 ± 0.06 μg/dl (A3) and 0.14 ± 0.06 μg/dl (B3); in Hiora mouthwash subgroup was 0.10 ± 0.06 μg/dl (A4) and 0.12 ± 0.05 μg/dl (B4). Conclusions: The mean ion release was the highest in deionized water (control group) followed by chlohex, Phos-Flur, and Hiora in both Group A and Group B. Ion leaching from bonded brackets was less compared to nonbonded brackets in all different mouthwashes except in the control group. However, this difference was statistically insignificant (P > 0.05) between all the groups.